2018
DOI: 10.1051/mmnp/2018036
|View full text |Cite
|
Sign up to set email alerts
|

Net reproduction functions for nonlinear structured population models

Abstract: The goal of this note is to present a general approach to define the net reproduction function for a large class of nonlinear physiologically structured population models. In particular, we are going to show that this can be achieved in a natural way by reformulating a nonlinear problem as a family of linear ones; each of the linear problems describing the evolution of the population in a different, but constant environment. The reformulation of a nonlinear population model as a family of linear ones is a new … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…To this end, for every fixed u ∈ Y 0 + we define the net reproduction number as Note that naturally R : Y 0 + → R + can be considered as a functional, and so we may call it the net reproduction functional, see also [21] for more details in this direction. Also note that for the specific model we considered here we had to formally define R at the extinction steady state (zero population density) separately, since F 1 is not defined at 0 in general.…”
Section: Boundary Perturbations -Through a Concrete Examplementioning
confidence: 99%
See 1 more Smart Citation
“…To this end, for every fixed u ∈ Y 0 + we define the net reproduction number as Note that naturally R : Y 0 + → R + can be considered as a functional, and so we may call it the net reproduction functional, see also [21] for more details in this direction. Also note that for the specific model we considered here we had to formally define R at the extinction steady state (zero population density) separately, since F 1 is not defined at 0 in general.…”
Section: Boundary Perturbations -Through a Concrete Examplementioning
confidence: 99%
“…Indeed, net reproduction numbers, functions and functionals play an important role when studying the existence and the local asymptotic stability of equilibria of physiologically structured population dynamical models, for more details see e.g. the recent papers [4,5,15,19,21,22,23,35,36].…”
Section: Boundary Perturbations -Through a Concrete Examplementioning
confidence: 99%
“…As a result, modelling population dynamics, it is natural to assume that the vital rates such as fertility, mortality, and growth rates of individuals depended on its body size (see [7,9]). In [6], the authors investigated the net reproduction functions for nonlinear structured population models. Moreover, construction of a net reproduction function in structured populations is crucial for understanding stability of their stationary states (see [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…nutrition), age, sex, space and other factors (Dwyer et al 1997;Keith and Mitchell-Olds 2013;Sorci et al 2013) and it was shown to strongly affect the course of evolution, in particular resulting in evolutionary branching (Pugliese 2011;Lion and Metz 2018). The importance of considering the heterogeneity of host is closely related to the current trend in modelling in population dynamics which highlights the necessity of studying physiologically structured populations (Metz and Diekmann 1986;Calsina and Farkas 2014;Farkas 2018;Farkas and Hagen 2007;Magal et al 2010;de Roos and Persson 2013).…”
Section: Introductionmentioning
confidence: 99%